Patrimônio edificado pela CCEVFRGS: identificação de unidades em Santa Maria/RS - Alcântara, Marina de (2015)
This dissertation has as general objective to identify the buildings of the Cooperativa de Consumo dos Empregados da Viação Férrea do Rio Grande do Sul producing an inventory of the main built properties occupied by the institution in the city of Santa Maria - RS. The Cooperativa de Consumo dos Empregados da Viação Férrea do RS was founded in 1913, locating its office in Santa Maria. The project aimed the social, economic and cultural life of its members, forming a kind of network that covered much of the state, locating its subsidiaries in several cities. Through the buildings occupied with its business operations, health and education, it was responsible for the transformation of spaces in urban and regional scale. In Santa Maria - RS the main buildings of the institution were located, such as the Men's and Women s Arts and Crafts Schools, Health House, the head office as well as an apparatus of Stores, Pharmacies, Butchers, Bakeries and small factories distributed in three different areas of the city, always linked to the core railway workers. From the top of its management until its complete decay influenced by different factors, the Cooperativa de Consumo dos Empregados da Viação Férrea do Rio Grande do Sul built a vast patrimony that was gradually being degraded. In the special case of Santa Maria, some buildings were expropriated via lawsuits and others sold to end debts. The proposed inventory has as one of its objectives the organization of data currently scattered about its built environment contributing to the discussion of its value as symbols of the railway workers mainly in Santa Maria. To construct this inventory, this dissertation rescued the history of organization and decay of the institution in Santa Maria and in the state, still addressing aspects of the city's development and its relation to rail transport. In order to base this paper it is presented theoretical references on topics such as culture, memory and cultural heritage as well as issues raised about preservationist policies. This study points the existence of 18 buildings occupied by the Cooperativa de Consumo dos Empregados da Viação Férrea do Rio Grande do Sul in Santa Maria, of which only 15 are identified as adopting registration methodology to producing an inventory using as reference models of the Instituto do Patrimônio Histórico e Artístico do Estado do Rio Grande do Sul and the Instituto do Patrimônio Histórico e Artístico Nacional, producing an amount of 10 files.